New insights into Trypanosoma cruzi genetic diversity, and its influence on parasite biology and clinical outcomes - Silvestrini, Marina Malheiros Araújo; Alessio, Glaucia Diniz; Frias, Bruna Estefânia Diniz; Sales Júnior, Policarpo Ademar; Araújo, Márcio Sobreira Silva; Silvestrini, Carolina Malheiros Araújo; Brito Alvim de Melo, Gustavo Eustáquio; Martins-Filho, Olindo Assis; Teixeira-Carvalho, Andréa; Martins, Helen Rodrigues (Frontiers in Immunology, 2024)
Chagas disease, caused by Trypanosoma cruzi, remains a serious public health problem worldwide. The parasite was subdivided into six distinct genetic groups, called “Discrete Typing Units” (DTUs), from TcI to TcVI. Several studies have indicated that the heterogeneity of T. cruzi species directly affects the diversity of clinical manifestations of Chagas disease, control, diagnosis performance and susceptibility to treatment. Thus, this review aims to describe how T. cruzi genetic diversity influences the biology of the parasite and/or clinical parameters in humans. Regarding geographic dispersion of T. cruzi, evident differences were observed in the distribution of DTUs in distinct areas. For example, TcII is the main DTU detected in Brazilian patients from the central and southeastern regions, where there are also registers of TcVI as a secondary T. cruzi DTU. An important aspect observed in previous studies is that the genetic variability of T. cruzi can impact parasite infectivity, reproduction and differentiation in the vectors. It has been proposed that T. cruzi DTU influences the host immune response and affects the disease progression. Genetic aspects of the parasite play an important role in determining which host tissues will be infected, thus heavily influencing Chagas disease's pathogenesis. Several teams have investigated the correlation between T. cruzi DTU and the reactivation of Chagas disease. In agreement with these data, it is reasonable to suppose that the immunological condition of the patient, whether or not associated with the reactivation of the T. cruzi infection and the parasite strain, may have an important role in the pathogenesis of Chagas disease. In this context, understanding the genetic of T. cruzi and its biological and clinical implications will provide new knowledge that may contribute to additional strategies in the diagnosis and clinical outcome follow-up of Chagas disease patients, in addition to the reactivation of immunocompromised patients infected by T. cruzi.